Peningkatan Ikatan Adhesi terhadap Pengurangan Retak Lapisan PVA pada Ti-6Al-4V ELI untuk Aplikasi Biomedis - Ardhy, Sanny; Islahuddin, Islahuddin; Putra, Meiki Eru; Hamzah, Reodhy; Zulfikar, Zulfikar (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
The lack of adhesion bonding of the hydroxyapatite (HA) coating layer on the surface of implant material can cause the coating layer to peel off during implantation and will increase the risk of metallic ion release to human body and may also to increase inflammatory effect and slow down the osseointegration process. In order to increase the adhesion of HA coated Ti-6Al-4V ELI by adding Zirconium Oxide (ZrO2) into the coating layer.The coating process of the HA suspension with addition ZrO2 into Ti-6Al-4V ELI sample surfaces was conducted by using dip-coating method. The samples were then heated at 800, 900, and 950 °C. The improvement of adhesion coating was correlated by calculating the removed area. The low value of removed coating area indicated the adhesion coating is good. The test specimen with the addition of ZrO2, has a removed area fewer than the test specimen without the addition of PVA- ZrO2 has. This shows that the test specimen with the addition of ZrO2 has good coating adhesion.The addition of PVA- ZrO2 to the HA suspension increases adhesion bonding of the coating layer, as indicated by the low removed area as compared to that of without PVA- ZrO2 coating.